FAKTOR-FAKTOR YANG MEMPENGARUHI ANJLOKNYA IHSG - Johni Eka Putra; Septiana Na'afi; Dewi Mariam Widiniarsih; Imam Baidlowi; Siti Mariani Basannang (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine and test the effect of BI Rate, rupiah exchange rate, inflation and Dow Jones index on the Composite Stock Price Index (IHSG). This study uses secondary data obtained from the US Energy Information Administration, Bank Indonesia, and Yahoo Finance from January 2020 to December 2023. In this study, the data analysis methods used are descriptive analysis, classical assumption test, and multiple linear regression analysis with a sample size of 48 samples. The results of the study indicate that the BI Rate has a significant effect on the fall of IHSG. The rupiah exchange rate has a significant effect on the fall of IHSG. The Dow Jones index has a significant effect on the fall of IHSG. While inflation does not have a significant effect on the fall of IHSG.